2020
DOI: 10.21203/rs.3.rs-40713/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recurrent Uterine Tumors Resembling Ovarian Sex-cord Tumors with the Growth Regulation by Estrogen in Breast Cancer 1-Nuclear Receptor Coactivator 2 Fusion Gene: A Case Report and Literature Review

Abstract: Background: Uterine tumors resembling ovarian sex-cord tumors (UTROSCTs) are rare mesenchymal neoplasms predominantly arising in perimenopausal and postmenopausal women. UTROSCTs with growth regulation by estrogen in breast cancer 1 (GREB1)-rearrangement or GREB1-rearranged uterine tumors are exceptionally rare, with only 12 previously reported cases. Here, we report a case of UTROSCT with the GREB1-nuclear receptor coactivator 2 (NCOA2) fusion gene. Case Presentation: A 57-year-old woman presented with a 10.0… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…For comparison, only 3 of 22 ESR1-rearranged UTROSCTs have developed these adverse events, and it is interesting that all the 3 cases harbored ESR1-NOCA2 fusion and showed extensive rhabdoid morphology (4). These collective findings suggest that both GREB1 and ESR1 fused UTROSCTs could behave in an aggressive manner despite their general indolence, while tumors harboring GREB1 rearrangements seem to be more aggressive than those with ESR1 fusions (3,4,(11)(12)(13). However, it is also possible that the 3′ fusion genes, particularly NCOA2, could impart the possibility of recurrence of aggressive outcomes, as 7 of the 9 cases of UTROSCT with adverse outcomes contained NCOA2 as the 3′ partner gene (3,4,(11)(12)(13)18,19).…”
Section: Uterine Tumor Resembling Ovarian Sex Cord Tumormentioning
confidence: 93%
See 2 more Smart Citations
“…For comparison, only 3 of 22 ESR1-rearranged UTROSCTs have developed these adverse events, and it is interesting that all the 3 cases harbored ESR1-NOCA2 fusion and showed extensive rhabdoid morphology (4). These collective findings suggest that both GREB1 and ESR1 fused UTROSCTs could behave in an aggressive manner despite their general indolence, while tumors harboring GREB1 rearrangements seem to be more aggressive than those with ESR1 fusions (3,4,(11)(12)(13). However, it is also possible that the 3′ fusion genes, particularly NCOA2, could impart the possibility of recurrence of aggressive outcomes, as 7 of the 9 cases of UTROSCT with adverse outcomes contained NCOA2 as the 3′ partner gene (3,4,(11)(12)(13)18,19).…”
Section: Uterine Tumor Resembling Ovarian Sex Cord Tumormentioning
confidence: 93%
“…In contrast, tumors with ESR1 fusions tend to occur in premenopausal females and are predominantly composed of sex cord-like elements; they may contain foamy or lipidized cells and eosinophilic or Leydig-like cells, and are more likely to express multiple specific sex cord markers (3,4,(10)(11)(12)(13). On the basis of the current body of knowledge, it has been suggested that ESR1rearranged UTROSCTs and uterine tumors with GREB1 fusions are better to be regarded as a unifying entity despite significant heterogeneity, containing variable sex cord-like elements (3,13). With regard to the prognosis, including the current case and those have previously been called as GREB1-rearranged uterine sarcomas (11,18), there are a total of 16 cases of GREB1-fused uterine tumors/UTROSCTs have been described to date, among which 6 (4 with NCOA2, 1 with CTNNB1, and 1 with NR4A3) have experienced local recurrence or distant metastasis within a follow-up period ranging from 3 wk to 14 y (3,(11)(12)(13)18,19).…”
Section: Uterine Tumor Resembling Ovarian Sex Cord Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic fusions so far identified in UTROSCT are summarized in Table 1 3,18‐25 . The domains included in the chimeric proteins are illustrated in Figure 1.…”
Section: Molecular Characterization Of Utrosctmentioning
confidence: 99%
“…Indeed, 6 UTROSCT with local or distant recurrence harbored GREB1 fusions (4 with NCOA2 , 1 with CTNNB1 , and 1 with NR4A3 ; see Table 1). 3,19‐21,23,25 The first case (with GREB1‐NCOA2 ) developed lung metastases, 2 and 11 years after the initial excisional surgery. Two subsequent patients with GREB1‐NCOA2 tumors underwent pelvic recurrence at 66 months and 30 months, respectively.…”
Section: Possible Correlation Between Fusion Types and Biological Aggmentioning
confidence: 99%